The Role of Statins in the Management of Delirium: Recent Advances - Chen, Junhui; Wang, Yuhai; Hu, Ximin; Li, Mingchang; Xiong, Kun; Zhang, Zhaocai; Chen, Qianxue (CNS & Neurological Disorders - Drug Targets, 2021)
Delirium is a clinical syndrome characterized by a temporary organic mental disorder, as well as abnormal attention and cognition. It is a very common, serious, and costly disease with high misdiagnosis and death/disability rates, especially for older patients after surgery. Several factors, such as systemic neuroinflammation, neurotransmitters, cerebral hypoperfusion and microthrombosis, contribute to the progress of delirium; however, the exact pathophysiologic mechanisms are not well known. Therefore, there are no specific therapeutic approaches that can treat delirium effectively. Statins, as inhibitors of 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase, have been identified as potential medications for the treatment of delirium because they can significantly reduce the incidence of delirium. The major objective of the current review is to summarize recent advances in the understanding of the effects and mechanisms of statins on delirium. In basic research, statins can alleviate delirium via attenuation of neuroinflammation, neurotransmitters, cerebral hypoperfusion, and microthrombosis, which may highlight their potential clinical application for the treatment of delirium. Despite this, the clinical effects of statins still provoke debate.
Keywords: inflammation